2022
DOI: 10.1108/lodj-04-2021-0156
|View full text |Cite
|
Sign up to set email alerts
|

How leader bottom-line mentality relates to employee innovation: a cross-layer model mediated by psychological contract breach

Abstract: PurposeThis study aims to examine how and when leader bottom-line mentality (BLM) affects employee innovation (EI) in the context of Chinese organisations in which psychological contract breach (PCB) is a mediator and moral identity (MI) is a moderator.Design/methodology/approachThe authors distributed the questionnaires to technology and culture firms in 2 waves and obtained a sample of 308 employees in 56 teams. The authors used the hierarchical linear model (HLM) and bootstrap method for the hypothesis test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Furthermore, employees who share the values of the organization responded to leader BLM with weaker relative deprivation and mitigated negative effects on psychological safety. Additionally, research has found that employees higher in moral identity respond to leader BLM with a stronger breach in their psychological contracts (i.e., a failure to fulfill obligations owed to employees; Rousseau, 1995) that then reduces their innovation (Liu, Fan, Liu, & Long, 2022).…”
Section: An Overview Of Leader Blmmentioning
confidence: 99%
“…Furthermore, employees who share the values of the organization responded to leader BLM with weaker relative deprivation and mitigated negative effects on psychological safety. Additionally, research has found that employees higher in moral identity respond to leader BLM with a stronger breach in their psychological contracts (i.e., a failure to fulfill obligations owed to employees; Rousseau, 1995) that then reduces their innovation (Liu, Fan, Liu, & Long, 2022).…”
Section: An Overview Of Leader Blmmentioning
confidence: 99%
“…Leaders’ role remained significant for performance pressure, employee’s actual performance and un-ethical behavior ( Zhang et al, 2021 , 2022 ; Liu et al, 2022 ). Ambitious leaders are needed by organizations ( Steffens et al, 2018 ).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Besides, adoption of BLM decreases leaders’ engagement of ethical leadership and goal-focused leader behavior (Rice and Reed, 2021) and increases leaders’ engagement of abusive supervision (Rice and Day, 2022). Regarding to employee behaviors and performance, supervisor BLM was found to increase work–family conflict (Quade et al , 2021), unethical pro-leader behavior (Mesdaghinia et al , 2019), unethical pro-organizational behavior (Farasat and Azam, 2022; Zhang et al , 2020) and cheating behavior (Farasat et al , 2021), as well as decrease employee innovation (Liu et al , 2022) and employee performance (Quade et al , 2020), team cohesiveness (Riisla et al , 2021) and team performance (Lin et al , 2021). Recent research on BLM has taken a more functional or balanced view of supervisor BLM by investigating both its beneficial and detrimental organizational outcomes, such as increased employee task performance and also lead to unethical pro-organizational behavior (Babalola et al , 2021), increased employee thriving at work and insomnia outside of work (Babalola et al , 2022a, 2022b) and reduced customer incivility, enhanced customer service performance and instigation of customer-directed unethical conduct (Babalola et al , 2020), increased employee work performance and also lead to knowledge hiding toward coworkers (Zhang et al , 2021).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%